FEATURES OF PARENTS’ EXPERIENCE OF THE MARRIAGE AND DIVORCE PROCESS OF FAMILY DISPUTES - Kozlova, Anna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article carries out a theoretical and empirical analysis of the study of the peculiarities of the experience and behavior of parents during divorces in family disputes related to raising a child. The aim of the study. To reveal the specifics of parents’ experience of divorce, changes in their behavior as a result of the court process in order to understand how it affects the psycho-emotional state and development of the child in such conditions in order to ensure his best interests. The results. In the course of the research, a number of important decisions of the Supreme Court of Ukraine, decisions of the European Court of Human Rights (ECtHR) were analyzed, based on which the best interests of the child in family disputes were determined, and the specifics of the marriage and divorce process in family disputes were identified, namely: through what stages of understanding the need for divorce and the impossibility of continuing the relationship go through, what stages of emotional experiences parents go through in divorce, the presence and level of conflict of the divorce process, which significantly affects the behavior of parents and, accordingly, changes the focus of their attention from the educational process to the judicial process, strategies of parental behavior in the legal process, as well as the stage of experiencing the legal process in family disputes. Conclusions. According to the results of the research, it was found that there is an excessive load on the mental activity of parents, which is associated with: the process of the breakup of marital relations, the specifics of experiencing a divorce, the stages of experiencing a legal process, in which parents develop models of "attack" and "defense" behavior, the specifics of implementation of one’s own needs in the court process and the degree of conflict associated with participation in raising a child. As a result, this leads to a negative impact on the child, in that the court process becomes part of the child’s life, making it impossible to provide a favorable environment for the upbringing and development of the child